Use of Renin–Angiotensin–Aldosterone System Inhibitors in Older Patients with Heart Failure and Reduced Ejection Fraction - Davide Stolfo; Gianluigi Savarese (Cardiac Failure Review)
Patients enrolled in randomised clinical trials may not be representative of the real-world population of people with heart failure (HF). Older patients are frequently excluded and this limits the strength of evidence which supports the use of specific HF treatments in this patient group. Lack of evidence together with fear of adverse effects, drug interactions and lower tolerance may lead to the undertreatment of older patients and a less favourable outcome. Renin–angiotensin–aldosterone system (RAAS) inhibitors are the cornerstone of treatment for patients with HF with reduced ejection fraction (HFrEF), but despite the class I recommendation for all patients regardless of age in the guidelines, there are signs that RAAS inhibitors are underused among older patients. Large registry- based studies suggest that RAAS inhibitors may be at least as effective in older patients as younger ones, but these findings need to be confirmed by randomised clinical trials.